2000
DOI: 10.1095/biolreprod62.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Stress Increases Prolyl cis/trans Isomerase Activity and Expression of Cyclophilin 18 in Rabbit Blastocysts

Abstract: The peptidyl-prolyl cis/trans isomerase (PPIase) activity and the expression of cyclophilins were studied in 6-day-old rabbit preimplantation embryos cultured under physiological and increased oxygen concentrations of 5% and 20% O(2), respectively. The PPIase activity was completely inhibited by cyclosporin A (CsA). The inhibitor of FK506-binding proteins, rapamycin, had no effect on the PPIase activity, indicating that the PPIase activity in rabbit blastocysts originates from cyclophilins. Using CsA affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…Interestingly, suppression of cyclophilin A, the cytosolic isoform of the family of PPIases that bind cyclosporin A, has been reported in markedly sensitize cells to oxidative stress (50). An involvement of PPIase activity in oxygen defense has been reported for cyclophilin 18 in rabbit blastocysts (51). The thiol-specific antioxidant protein Aop1 has also been reported to bind human cyclophilin 18 (52).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, suppression of cyclophilin A, the cytosolic isoform of the family of PPIases that bind cyclosporin A, has been reported in markedly sensitize cells to oxidative stress (50). An involvement of PPIase activity in oxygen defense has been reported for cyclophilin 18 in rabbit blastocysts (51). The thiol-specific antioxidant protein Aop1 has also been reported to bind human cyclophilin 18 (52).…”
Section: Discussionmentioning
confidence: 99%
“…From bacteria to humans, they are ubiquitously, abundantly expressed and show a very strong conservation of their PPIase domain (1,11). Cyclophilins have been localized in different cell compartments, and their poorly understood functions have been so far linked to multiple cellular processes, such as protein folding (12), trafficking (13), chaperone activity (14), oxidative stress response (15), and functional arrangement of components within receptor complexes (16). The abundance and ubiquitous expression of these proteins have suggested that their function might be pleiotropic, but a growing body of evidence points toward the fact that different cyclophilins function in a restricted and specific manner.…”
mentioning
confidence: 99%
“…In adipocytes and myocytes GLUT4 translocation is the rate-limiting step of insulinstimulated glucose uptake (Saltiel 2001). In preimplantation embryos GLUT4 expression has been shown for bovine (Navarrete Santos et al 2000, Augustin et al 2001, rat (Korgun et al 2001) and rabbit (Navarrete blastocysts. The expression data from mouse preimplantation embryos are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…follicle-stimulating hormone (Ovagen, Immuno-Chemical Products, Auckland, New Zealand, or Folligon, Intervet, Boxmeer, The Netherlands). Mating, embryo recovery (Navarrete Santos et al 2000) and embryo culture (Kietz & Fischer 2003) were performed as described. On days 3, 4 and 6 post coitum (p.c.)…”
Section: Embryo Recovery and In Vitro Culturementioning
confidence: 99%
See 1 more Smart Citation